Better boardrooms repairing corporate governance for the 21st century - Meredith, Patricia, 1955- (University of Toronto Press, 2020)
"This is the third of three books authored by award-winning author Patricia Meredith. Her first book, Catalytic Governance: Leading Change in the Information Age (co-authored by Steve Rosell and Ged Davis) set out a process for leading transformative change, based on the authors' experience with the Canadian Task Force for the Payments System Review. Her second book, Stumbling Giants: Transforming Canada's Banks for the Information Age (winner of the 2018 Donner Prize and co-authored with James Darroch) highlighted how ill-prepared the Canadian banks are for the technology tsunami overtaking financial services. To regain their reputation as vibrant enablers of economic growth, Better Boardrooms proposes that a broad cross-section of Canadians - policy makers and regulators, customers, suppliers, investors and, not least, bankers themselves - work together to create a banking system better suited to the twenty-first century. This new model of governance is based on a collaborative approach which ensures all relevant voices are heard. As boundaries between industries blur and stakeholders gain greater access to information, it is vital that policymakers and regulators, customers and suppliers, investors and managers work together to fix Better Boardrooms."--